مدى التزام المؤسسات الصناعية بالإفصاح البيئي في ظل بيئة الاعمال الحديثة - لصاق, حيزية (جامعة الوادي - University of Eloued, 2024)
هدفت هذه الدراسة إلى إظهار مدى التزام المؤسسات الصناعية بالإفصاح البيئي، إذ يعتبر مؤشرا على ما إذا كانت المؤسسات مدركة للقضايا البيئية التي قد تؤثر في وجودها، إذ يعتبر مهما لمستخدموا القوائم المالية للوقوف على الأحداث البيئية وجهود المؤسسات نحو إدارة البيئة والآثار المالية المترتبة عليها. حيث قمنا بإسقاط هذه الدراسة على مؤسسة الإسمنت بالسور الغزلان لولاية البويرة والتي تناولت مدى التزام المؤسسة بالإفصاح البيئي، والتعرف على أهم الصعوبات والمعوقات التي تحول دون قيامها بالإفصاح البيئي، وذلك من خلال توزيع 35 استبانة على موظفي الأقسام والمصالح ذات العلاقة بالموضوع، وخلصت الدراسة إلى أن المؤسسة لا تقوم بالإفصاح البيئي، وهناك جملة من المعوقات التي حالت دون القيام مؤسسة محل الدراسة بالإفصاح البيئي. This study aimed to show the extent to which industrial enterprises are committed to environmental disclosure, as it is an indicator of whether the enterprises are aware of the environmental issues that may affect their existence, as it is important for users of financial statements to find out about environmental events and the efforts of enterprises towards managing the environment and the financial implications thereof. We projected this study on the Cement Corporation in Al-Sur Al-Ghazlan in the state of Bouira, which dealt with the extent of the organization's commitment to environmental disclosure, and to identify the most important difficulties and obstacles that prevent it from carrying out environmental disclosure, through the distribution of 35 questionnaires to employees of departments and interests related to the subject, and the study concluded that The institution does not perform environmental disclosure, and there are a number of obstacles that prevented the institution under study from environmental disclosure.
The degree of commitment of industrial enterprises to environmental disclosure in light of the modern business environment
مقال
Keywords: الإفصاح البيئي ; الأداء البيئي ; الأثار البيئية ; بيئة الأعمال الحديثة ; المؤسسات الصناعية: environmental disclosure; environmental performance; environmental effects; modern business environment; industrial enterprises.